A STUDY ON THE INFLUENCING FACTORS OF CUSTOMER SATISFACTION OF ALIPAY PLATFORM COMMERCIAL INSURANCE - Zou, Ruocheng (Journal of Buddhist Education and Research (JBER), 2024)
This paper aimed to explore the factors affecting consumer satisfaction in China's Internet insurance industry, the commercial insurance of Alipay platform is mainly used, and the influencing factors produced by the characteristics of this platform are investigated to analyze the influence on customer satisfaction. This research mainly focuses on the Enjoy the e-Life insurance product, 722 valid data were collected from 756 respondents, and the tool is an online questionnaire. The collected data were analyzed by means of descriptive statistical analysis, correlation analysis, structural equation model analysis, etc, and find out the main problems of Alipay commercial insurance, and at the same time, with the help of the analysis of the key factors affecting customer satisfaction, to find specific methods and measures to improve and enhance customer satisfaction. This result revealed that the main factors affecting customer satisfaction were customer perceived quality, customer perceived value, customer expectation, and customer perceived service. In terms of perceived quality, the strengthening of high-quality cooperation and launch diversified products and the development of customized personalized new products were necessary For perceived value, improve cost performance and reduce deductibles; In terms of customer expectation, the research recommended the accuracy of publicity and reasonably guide expectations to be improved; In terms of perceived service, it was necessary to optimize the interface settings and strengthen data analysis.